2008
DOI: 10.1021/jf8016749
|View full text |Cite
|
Sign up to set email alerts
|

New Esters of Okadaic Acid in Seawater and Blue Mussels (Mytilus edulis)

Abstract: Marine algal toxins of the okadaic acid (OA) group can occur as diol esters and sulfated diol esters in algae and as fatty acid esters in shellfish. Several of these ester forms have been identified, but the most common procedure for detecting OA group toxin esters is by measuring the increase in parent toxin after alkaline hydrolysis. Use of this alkaline hydrolysis method led to the discovery of high levels of conjugates of OA and dinophysistoxins-2 (DTX2) in seawater and of OA, DTX1, and DTX2 in blue mussel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Cruz and co-workers suggested that different phytoplankton species can be associated with the production of specific enol esters and that sulfate derivatives of each reported diol-ester exist. In addition to diol-esters, a C8-triol OA derivative was more recently observed in seawater collected during a Dinophysis bloom in Norway (Torgersen et al, 2008a).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Cruz and co-workers suggested that different phytoplankton species can be associated with the production of specific enol esters and that sulfate derivatives of each reported diol-ester exist. In addition to diol-esters, a C8-triol OA derivative was more recently observed in seawater collected during a Dinophysis bloom in Norway (Torgersen et al, 2008a).…”
Section: Introductionmentioning
confidence: 95%
“…The cells were rinsed on the sieve with fresh f/2 media, and kept wet to minimize breakage. The cells were washed into a 15-mL Falcon tube Tachibana and Scheuer, 1981;(2) Murata et al, 1982;(3) Larsen et al, 2007;(4) Yasumoto et al, 1985;(5) Marr et al, 1992 (6) Hu et al, 1995a;(7) Hu et al, 1995b;(8) Cruz et al, 2006;(9) Fernandez et al, 2003;(10) Suarez-Gomez et al, 2005;(11) Yasumoto et al, 1989;(12) Hu et al, 1992a;(13) Suarez-Gomez et al, 2001;(14) Miles et al, 2006;(15) Torgersen et al, 2008a;(16) Norte et al, 1994. using fresh f/2 media (13 mL), and the tube immersed in a water bath at 100 C for 5 min. The samples were frozen at À20 C, thawed at room temperature, and sonicated in a water bath (Fisher ultrasonic cleaner, Model FS30H) for 15 min before solid-phase extraction (SPE).…”
Section: Sample Preparation and Extraction Of Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a role in OA acylation was initially ascribed to bacteria present in the bivalve gut [46], it was later demonstrated that in mussels the OA is primarily transformed in the endoplasmic reticulum [47]. Acylation seems to play a major role in OA depuration, yet, further studies are still needed in order to ascertain the mechanisms underlying depuration rates of different toxins in different bivalve species [48]. …”
Section: Response Strategies To Okadaic Acid In Marine Invertebratesmentioning
confidence: 99%
“…Two new pectenotoxins, 36S-PTX-12 and 36R-PTX-12 in Dinophysis spp, occurred as a pair of equilibrating diasteroisomers that were different from PTX-2 [76]. With the use of alkaline hydrolysis, several groups of new conjugates of okadaic acid (OA) and dinophysisoxins-2 (DTX2) in seawater were identified [77]. A C8-dio ester, a C9-dio ester, and new C8-triol ester of OA were characterized using QIT with multiple stages of mass spectrometry (HPLC-MS 2 , MS 3 , and MS 4 ) in combination with various derivatization procedures.…”
Section: Recent Development In Instrumental Analysis Of Algal Toxinsmentioning
confidence: 99%